2020
DOI: 10.1016/j.compscitech.2020.108194
|View full text |Cite
|
Sign up to set email alerts
|

Combined loadings after medium velocity impact on large CFRP laminate plates: Tests and enhanced computation/testing dialogue

Abstract: The development and certification of aeronautical composite structures is still largely based on the pyramid of tests. This approach is extremely costly in terms of number of tests, especially at the level of coupons. Moreover, these tests are highly conservative, under uniaxial loading, and do not represent the actual behavior at structure scale. To overcome these drawbacks, a new methodology has been developed at the Institut Cl� ement Ader, which uses a complex loading test rig for technological specimens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Currently, the available data and information in the literature with respect to the low-velocity impact (LVI) performance of carbon fibre reinforced thermoplastic polymer (CFRTP) is still limited, unlike carbon fibre reinforced thermosetting (CFRTS) composites [1,[10][11][12][13][14][15][16][17][18]. In fact, in the literature, much research has focused solely on glass fibre reinforced polymer (GFRP) [19].…”
Section: Characterisation Of Impact Behaviour Of Thermoplastic Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the available data and information in the literature with respect to the low-velocity impact (LVI) performance of carbon fibre reinforced thermoplastic polymer (CFRTP) is still limited, unlike carbon fibre reinforced thermosetting (CFRTS) composites [1,[10][11][12][13][14][15][16][17][18]. In fact, in the literature, much research has focused solely on glass fibre reinforced polymer (GFRP) [19].…”
Section: Characterisation Of Impact Behaviour Of Thermoplastic Compositesmentioning
confidence: 99%
“…Trellu et al [10] have previously reported the compression after impact (CAI) performance of unidirectional (UD) CFRTS (T700/M21 epoxy) at velocities ranging from 54 m/s to 110 m/s. This represents a small debris impact during aircraft take-off or landing.…”
Section: Characterisation Of Impact Behaviour Of Thermoplastic Compositesmentioning
confidence: 99%
“…To capture the failure scenario, the test bench was equipped with several measurement systems as shown in Figure 9. Stereo Digital Image Correlation (SDIC) is a very reliable method that has already been used on previous VERTEX tests [24][25] [34]. Moreover, SDIC can measure out-of-plane displacements and reconstruct a 3D shape evolution.…”
Section: Measurement Systemsmentioning
confidence: 99%
“…Serra studied the failure of carbon fibre reinforced polymer notched plates [25] [33]. Trellu studied the effect of low-velocity impacts on carbon fibre reinforced polymer plates under multiaxial loading [34].…”
Section: Introductionmentioning
confidence: 99%
“…Serra et al [42] presented the machine and the state of the art for this kind of intermediate multi-axial test rigs. Large notch behaviour [43] and residual strengths post impact [44] have been assessed for planar samples under combined loadings. This is a first step towards moving up one level of the test pyramid with stiffened samples to finally assess large damage behaviour phenomenology, representative of current fuselage sections, at moderate cost.…”
Section: Introductionmentioning
confidence: 99%